Dynamic performance analysis of turbine flow sensor based on CFD simulations. (October 2022) - Liu, Xu; Song, Wei; Chi, Qiushuang; Guo, Suna; Wang, Fan; Zhao, Zhiyue
Abstract: The research on the dynamic performance of flowmeters has great significance for the accurate measurement of flow onsite. A simulation method for dynamic characteristics of turbine flow sensor was proposed in this study. This method was used to investigate the dynamic performance of three turbine flow sensors with different diameters. The amplitude-frequency characteristic, phase-frequency characteristic, transfer function, and step response are analyzed based on the results of the simulation. The results indicate that turbine flow sensors can be analyzed as a first-order system. The frequency of pulse flow is the main factor affecting the sensor's performance. The phase difference increases as the frequency increases, and the maximum phase difference reaches 50°. The gain of the small-diameter turbine flow sensor is susceptible, while the phase difference and time constant of the large-diameter turbine flow sensor are susceptible. For step flow, the time constant generated by the negative step is larger than that by the positive step. The analysis results provide bases for evaluating the dynamic performance of turbine flow sensors used online. Highlights: A method based on 6DOF model and dynamic grid is used to simulate the dynamic performance of the turbine flow sensor . The time constant of the step response and the frequency characteristic of the impulse response are analyzed. The frequency of the pulsating flow has obvious influence on the dynamic response of the turbine flow sensor.